Assistência espiritual em enfermagem: a problemática e uma solução - Guimarães, Virgínia Catherine Fuchs (1984)
This work, having the purpose of offering subsidies which might enrich the nurse's ability to give effective spiritual nursing care, discusses the problem situation in this area, and proposes a possible solution for it. Since the problem situation involves the spiritual needs of nurses as well as patients, an attempt is made to approach both. The spiritual dimension of Man, seen as the level where an interpersonal relationship with God can be established and from which the fruit of that relationship can be conmunicated to others, is described in detail. The basic spiritual needs of Man and their fulfillment as described in the work, are illustrated by the author's own personal story. It is at this point that the author describes the specific solution which she has found to be effective in her own life and believes to be applicable in the assistance of the spiritual needs of others. A detailed description of this application is then presented as a proposal for effective spiritual nursing care.